Non-targeted Metabolomic Analysis of Differences in the Composition of Different Rice Varieties for Baijiu Production - LIU Maoke, TIAN Xinhui, LIU Yao, TANG Yuming, QIN Jian, FENG Jun, LIU Chengyuan (Shipin Kexue)
Non-targeted metabolomics was used in order to investigate the differences in the metabolite composition of two varieties of Baijiu-brewing rice (JKY and PXY) and their influence on Baijiu brewing. A total of 4 159 metabolites were detected in both rice samples, mainly including lipids and lipid-like molecules, organoheterocyclic compounds, organic acids and their derivatives. A comparison between PXY and JKY yielded 326 differential metabolites (variable importance in projection (VIP) > 1 and P < 0.05), including the major components of Baijiu, such as lactic acid, ferulic acid and fumaric acid, as well as important substrates that supported brewing microorganism growth, such as melibiose, maltose, glucose and lactulose. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis of differential metabolites identified 16 significantly differential biological pathways (P < 0.05), of which 14 were assigned to metabolic functions, including those related to Baijiu brewing such as galactose metabolism, the biosynthesis of unsaturated fatty acids, fatty acid biosynthesis, and butanoate metabolism. These results offer a better understanding of the relationship between raw materials and Baijiu brewing, thereby providing a basis for selecting and promoting high-quality raw materials.